Polystyrene-coated NaBiF4 hollow up-conversion nanoparticles and preparation method thereof
By converting to the surface of nano particles on the surface of Nabif4, the polystyrene surface is used, and the pyramnol polymerization is used to use Yonghong Y to form a cover layer to solve the problem of easy decomposition and fluorescent spectrum multiplier in the water environment in the water environment to achieve the realization The stability and luminous performance of nano particles are improved.
Patent Information
- Application Number
- CN202411496090.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The synthesis conditions of existing upconverted luminescent materials such as NaYF4 are harsh, costly, and have small specific surface area of solid particles and low luminescence efficiency. NaBiF4 materials are easy to decompose in water environments, and the multimodality of fluorescence spectral limits its application.
By converting the surface of nanoparticles on the surface of Nabif4 hollow, the polystyrene surface is used to form a polystyrene covering NABIF4 hollow conversion of nanoparticles. And the multipiatedness of lighting through fluorescent resonance energy.
Improved the stability and luminous performance of Nabif4 up conversion nanoparticles, keeping it stable in the aqueous solution environment, and improving the peak of light, transformed into a single red light emitting, and enhanced the light emitting intensity.
Smart Images

Figure CN119371970A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of up-conversion luminescent materials, and in particular relates to a polystyrene-coated NaBiF4 hollow up-conversion nanoparticle and a preparation method thereof. Background Art
[0002] Upconversion nanomaterials have the characteristics of strong photostability, long fluorescence lifetime, and no background autofluorescence interference, and are widely used in near-infrared detection / photothermal therapy / temperature sensing. However, the synthesis conditions of the currently widely used commercial upconversion luminescent materials (such as NaYF4, etc.) are relatively harsh, and usually require the use of high temperatures above 300°C for a long time. And the use of rare earth yttrium (Y) as a matrix also requires the consumption of more rare earth materials, which is costly. In addition, the morphology of NaYF4 is mainly solid solid particles with a small specific surface area, which is not conducive to the utilization of incident light and has low luminescence efficiency.
[0003] Hollow structure nanomaterials have higher specific surface area and theoretically have higher light collection efficiency, and are expected to achieve better luminescence performance than traditional solid particles. Among them, NaBiF4 material is an emerging upconversion matrix in recent years, and the bismuth (Bi) element is not a rare earth element, the production cost is low, and it is non-toxic to the human body, so it has attracted widespread attention from researchers. However, the NaBiF4 matrix itself is prone to decomposition in an aqueous environment, resulting in weakened or even disappearance of the luminescence performance. In addition, like NaYF4, the fluorescence spectrum of NaBiF4 upconversion particles will have multiple peaks at the same time. This multi-peak nature will limit its further application in display, laser and imaging fields. Therefore, it is very necessary to explore new upconversion nanomaterials and their preparation methods. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles. By coating polystyrene on the surface of NaBiF4 hollow upconversion nanoparticles, not only can the NaBiF4 hollow upconversion particles remain stable in an aqueous solution environment, but also the multi-peak nature of the upconversion luminescence can be greatly improved, thereby converting multi-wavelength emission into a single red light emission.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The invention provides a polystyrene-coated NaBiF4 hollow upconversion nanoparticle. The nanoparticle is cubic or nearly spherical in shape, has an obvious cavity structure in the middle, has a diameter of 100 to 300 nanometers, a shell thickness of 5 to 15 nm, and has good crystallinity.
[0007] The present invention also provides a method for preparing the polystyrene-coated NaBiF4 hollow upconversion nanoparticles, which comprises the following steps:
[0008] S1, mixing bismuth nitrate, ytterbium nitrate, erbium nitrate, sodium nitrate, a ketone-containing surfactant and an ethylene glycol solution to prepare a clear solution A;
[0009] S2, mixing ammonium fluoride and ethylene glycol solution to prepare a clear solution B;
[0010] S3, adding water to solution A to make it into a white suspension state, then adding solution B thereto, and then performing a hydrothermal reaction. After the reaction is completed, the solution is naturally cooled, and after washing and drying, NaBiF4 hollow upconversion nanoparticles can be obtained;
[0011] S4. Mix the NaBiF4 hollow upconversion nanoparticles of S3, styrene, eosin Y, triethanolamine and tetrahydrofuran, and then irradiate the mixed solution with near-infrared excitation light under ice bath conditions. After the reaction is completed, the polystyrene-coated NaBiF4 hollow upconversion nanoparticles can be obtained by washing.
[0012] The polystyrene-coated NaBiF4 hollow upconversion nanoparticles prepared by the method of the present invention have a high specific surface area and more excellent luminescence performance. The polystyrene shell coated on the surface can not only enable the NaBiF4 hollow upconversion nanoparticles to remain stable in an aqueous solution environment, but also greatly improve the multi-peak nature of the upconversion luminescence, thereby converting the multi-wavelength emission into a single red light emission.
[0013] The polystyrene-coated NaBiF4 hollow upconversion nanoparticles prepared by the method of the present invention are expected to be applied in the fields of display, laser and imaging.
[0014] Preferably, in S1, the ketone-containing surfactant is selected from polyvinylpyrrolidone (PVP), the average molecular weight of the PVP is 30000-60000, and the concentration of the PVP is preferably 50-150 mg / mL.
[0015] Preferably, in S1, the concentration of the bismuth nitrate in the ethylene glycol solution is 0.1-0.4 mol / L, the concentrations of the bismuth nitrate, ytterbium nitrate and erbium nitrate are: Bi:Yb:Er=78%:20%:2%, the mass ratio of the bismuth nitrate to sodium nitrate is 1:(2-5), and the concentration of the ketone-containing surfactant in solution A is 50-150 mg / mL.
[0016] Preferably, in S2, the concentration of ammonium fluoride in the ethylene glycol solution is 1-1.5 mol / L.
[0017] Preferably, in S3, the volume ratio of solution A to the added water is 0.5-2:1, and the volume ratio of solution A to solution B after adding water is 1:3-8.
[0018] Preferably, in S3, the temperature of the hydrothermal reaction is 90-180° C., and the time is 1-3 h.
[0019] Preferably, S1 is performed by stirring the bismuth nitrate, ytterbium nitrate, erbium nitrate, sodium nitrate, PVP and ethylene glycol solution, with a stirring speed of 700-1000 r / min and a stirring time of 20-40 minutes.
[0020] Preferably, in S4, the mass ratio of the NaBiF4 hollow upconversion nanoparticles to styrene is 1:10-40, the mass ratio of the NaBiF4 hollow upconversion nanoparticles to eosin Y is 20-50:1, the mass ratio of the NaBiF4 hollow upconversion nanoparticles to triethanolamine is 2-5:1, and the mass volume ratio of the NaBiF4 hollow upconversion nanoparticles to tetrahydrofuran is 20-50mg:1mL.
[0021] Preferably, in S4, the wavelength of the near-infrared excitation light is 980 nm, and the power is 0.5-1 W / cm 2 The irradiation time is 10-14h.
[0022] Preferably, in S4, the mixed solution is irradiated with near-infrared excitation light and stirred at a rate of 600-1000 r / min.
[0023] Preferably, in S4, the washing is centrifugal washing with ethanol, the centrifugal speed is 9000-10000 rpm, the time is 5-15 minutes, and the washing is performed more than 3 times in total.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention discloses a method for preparing a polystyrene-coated NaBiF4 hollow upconversion nanoparticle. By utilizing the difference in solubility of bismuth ions in ethylene glycol and some solvents (such as water, ethanol, carbon tetrachloride, etc.), liquid phase separation is artificially induced in a mixed solvent to form small droplets of water-in-oil, and hollow upconversion nanoparticles are prepared using this as a soft template, and then a ketone-containing surfactant is added to regulate the morphology of the upconversion nanoparticles. At the same time, since the single NaBiF4 upconversion particles themselves are prone to decomposition in an aqueous environment, the invention further utilizes eosin Y as an initiator to induce styrene to polymerize on the particle surface, and then grow into polystyrene-coated hollow NaBiF4 upconversion nanoparticles, thereby improving the stability of the NaBiF4 upconversion nanoparticles in an aqueous solution environment; at the same time, eosin Y converts the blue and green fluorescence originally emitted by the upconversion nanoparticles into a single red light emission through fluorescence resonance energy transfer, thereby greatly improving the multi-peak nature of the upconversion luminescence, so that it has broad application prospects in the fields of display, laser and imaging. In addition, the conditions for synthesizing the upconversion material of the invention are relatively mild, the production cost is low, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a transmission electron microscope image of the polystyrene-coated NaBiF4 hollow upconversion nanoparticles prepared in Example 1;
[0027] Figure 2 The X-ray diffraction pattern of the polystyrene-coated NaBiF4 hollow upconversion nanoparticles prepared in Example 1;
[0028] Figure 3 Comparison of the luminescence spectra of hollow NaBiF4 before and after being coated with a polystyrene shell;
[0029] Figure 4 This is a transmission electron microscope image of the polystyrene-coated NaBiF4 hollow upconversion nanoparticles prepared in Example 2. DETAILED DESCRIPTION
[0030] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0032] Example 1: A method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles
[0033] (1) 0.70 mmol bismuth nitrate, 0.25 mmol ytterbium nitrate, 0.05 mmol erbium nitrate, 2 mmol sodium nitrate, 500 mg PVP (average molecular weight 40,000) and 5 mL ethylene glycol solution were mixed in a 45 mL polytetrafluoroethylene-lined reactor liner and stirred until completely dissolved. At this time, the solution became clear and was recorded as solution A.
[0034] (2) Mix 24 mmol of ammonium fluoride and 20 mL of ethylene glycol and stir until clear, which is referred to as solution B;
[0035] (3) Add 5 mL of deionized water to solution A and stir until the solution becomes a white suspension at a stirring speed of 800 r / min for 30 min. Then add solution B to solution A, lock the reactor, and react for one hour at a stirring rate of 1000 r / min under hydrothermal conditions of 160°C. After natural cooling, collect the precipitate by centrifugation at a speed of 8000 r / min, wash it several times with anhydrous ethanol, and finally dry it in an oven at 60°C overnight to obtain NaBiF4 hollow upconversion particles.
[0036] (4) NaBiF4 hollow upconversion particles (80 mg), styrene (2.1 g, 20 mmol), eosin Y (1.94 mg, 3 μmol), triethanolamine (35.8 mg, 0.24 mmol) and 2 mL of tetrahydrofuran were mixed, and the resulting mixture was placed in a transparent glass bottle and placed in an ice bath. The mixed solution was then excited with near-infrared light (980 nm, 0.7 W / cm 2 ) for 12 h, and stirred at 800 r / min. After the reaction was completed, the nanoparticles were washed three times by centrifugation with anhydrous ethanol (10000 rpm, 10 min), and then dispersed in anhydrous ethanol to obtain polystyrene-coated NaBiF4 hollow upconversion nanoparticles.
[0037] like Figure 1 As shown in the figure, the morphology of the prepared polystyrene-coated NaBiF4 upconversion particles is cubic or nearly spherical, with an obvious cavity structure in the middle, the diameter of the particles is 100 to 300 nanometers, and the shell thickness is 5 to 15 nm. Figure 2 It can be seen from the X-ray diffraction pattern that the prepared polystyrene-coated NaBiF4 hollow upconversion nanoparticles have good crystallinity.
[0038] In addition, the fluorescence spectra of NaBiF4 hollow upconversion nanoparticles before and after being coated with polystyrene shells were tested using a fluorescence spectrometer. Figure 3 As shown, the fluorescence emitted by NaBiF4 upconversion particles under 980nm wavelength excitation has fluorescence peaks of three different colors (blue, green, and red), but the NaBiF4 upconversion particles after polystyrene coating only emit red light, which greatly improves the multi-peak nature of the upconversion nanoparticles and enhances the red fluorescence intensity by 1.5 times.
[0039] Example 2: A method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles
[0040] The preparation method is the same as that of Example 1, except that the amount of styrene added in step (4) is adjusted to 800 mg. The transmission electron microscopy image of the prepared polystyrene-coated NaBiF4 hollow upconversion nanoparticles is as follows: Figure 4 As shown, it can be seen that the morphology of the upconversion nanoparticles changes from cubic to nearly spherical, and the thickness of the coating shell becomes smaller.
[0041] In summary, the present invention utilizes the difference in solubility of bismuth nitrate in ethylene glycol and some solvents (such as water, ethanol, carbon tetrachloride, etc.) to artificially induce liquid phase separation in a mixed solvent to form small droplets of water-in-oil, and uses this as a soft template to prepare hollow upconversion nanoparticles, and then adds ketone-containing surfactants such as polyvinyl pyrrolidone (PVP) to regulate the morphology of the upconversion particles. At the same time, since the individual NaBiF4 upconversion particles themselves are prone to decomposition in an aqueous environment, the performance is unstable. The present invention further utilizes eosin Y as an initiator to induce styrene to polymerize on the particle surface, and then grow into polystyrene-coated hollow NaBiF4 upconversion nanoparticles. At the same time, eosin Y converts the blue and green fluorescence originally emitted by the upconversion nanoparticles into a single red light emission through the fluorescence resonance energy transfer effect, thereby greatly improving the multi-peak nature of the upconversion luminescence.
[0042] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A polystyrene-coated NaBiF4 hollow upconversion nanoparticle, characterized in that: The nanoparticles are cubic or nearly spherical in shape, have an obvious cavity structure in the middle, have a diameter of 100 to 300 nanometers, a shell thickness of 5 to 15 nanometers, and have good crystallinity.
2. The method for preparing the polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 1, characterized in that: The following steps are involved: S1, mixing bismuth nitrate, ytterbium nitrate, erbium nitrate, sodium nitrate, a ketone-containing surfactant and an ethylene glycol solution to prepare a clear solution A; S2, mixing ammonium fluoride and ethylene glycol solution to prepare a clear solution B; S3, adding water to solution A to make it into a white suspension state, then adding solution B thereto, and then performing a hydrothermal reaction. After the reaction is completed, the solution is naturally cooled, and after washing and drying, NaBiF4 hollow upconversion nanoparticles can be obtained; S4. Mix the NaBiF4 hollow upconversion nanoparticles of S3, styrene, eosin Y, triethanolamine and tetrahydrofuran, and then irradiate the mixed solution with near-infrared excitation light under ice bath conditions. After the reaction is completed, the polystyrene-coated NaBiF4 hollow upconversion nanoparticles can be obtained by washing.
3. The method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 2, characterized in that: In S1, the ketone-containing surfactant is selected from polyvinyl pyrrolidone, and the average molecular weight of the polyvinyl pyrrolidone is 30,000-60,000.
4. The method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 2, characterized in that: In S1, the concentration of the bismuth nitrate in the ethylene glycol solution is 0.1-0.4 mol / L, the concentrations of the bismuth nitrate, ytterbium nitrate and erbium nitrate are: Bi:Yb:Er=78%:20%:2%, the mass ratio of the bismuth nitrate to sodium nitrate is 1:(2-5), and the concentration of the ketone-containing surfactant in solution A is 50-150 mg / mL.
5. The method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 2, characterized in that: In S2, the concentration of ammonium fluoride in the ethylene glycol solution is 1-1.5 mol / L.
6. The method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 2, characterized in that: In S3, the volume ratio of solution A to the added water is 0.5-2:1, and the volume ratio of solution A to solution B after adding water is 1:3-8.
7. The method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 2, characterized in that: In S3, the temperature of the hydrothermal reaction is 90-180° C. and the time is 1-3 hours.
8. The method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 2, characterized in that: In S4, the mass ratio of the NaBiF4 hollow upconversion nanoparticles to styrene is 1:10-40, the mass ratio of the NaBiF4 hollow upconversion nanoparticles to eosin Y is 20-50:1, the mass ratio of the NaBiF4 hollow upconversion nanoparticles to triethanolamine is 2-5:1, and the mass volume ratio of the NaBiF4 hollow upconversion nanoparticles to tetrahydrofuran is 20-50mg:1m.
9. The method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 2, characterized in that: In S4, the wavelength of the near-infrared excitation light is 980nm and the power is 0.5-1W / cm 2 The irradiation time is 10-14h.
10. The method for preparing polystyrene-coated NaBiF4 hollow upconversion nanoparticles according to claim 2, characterized in that: In S4, the mixed solution is irradiated with near-infrared excitation light and stirred at a rate of 600-1000 r / min.